ANALISIS BUDAYA ORGANISASI, DISIPLIN KERJA, DAN PENGEMBANGAN SUMBER DAYA MANUSIA TERHADAP KINERJA PEGAWAI DENGAN MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING DI KANTOR PEMERINTAHAN KECAMATAN LUBUK BAJA BATAM - Siagian, Mauli (EDUTECH CONSULTANT, 2017)
This study aims to determine the direct effect of organizational culture on work motivation. The direct influence of work discipline on work motivation.Direct influence of human resource development on work motivation.The direct influence of work motivation on employee performance.Direct influence of organizational culture on employee performance.The direct influence of work discipline on employee performance.The direct influence of human resource development on employee performance.Indirect influence of organizational culture on employee performance through work motivation.The indirect influence of work discipline on employee performance through work motivation.Indirect influence of human resource development on employee performance through work motivation in Government Office of Lubuk Baja Sub-district Batam. The number of samples used in this study were 94 samples. The research method used is quantitative paradigm, processing and analysis of data collected by research instrument through questionnaire is to use path analysis with sotware tool SPSS Version 21. The result of this research is; Organizational culture has an insignificant effect on work motivation. Work discipline has a significant influence on work motivation. The development of human resources has an insignificant effect on work motivation. Organizational culture has an insignificant effect on employee performance. Work discipline has a significant effect on employee performance. The development of human resources has no significant effect on employee performance. Work motivation has a significant effect on employee performance. Organizational culture has a significant effect on employee performance through work motivation. Work discipline has a significant effect on employee performance through work motivation.